Empirical Contributions of Islamic Religious Education to the Cultivation of Noble Morality and Student Character Formation in the Paradigm of Holistic Education - Enung Herawati; Iskandar Mirza (UIN Sunan Gunung Djati Bandung, 2026)
Islamic religious education plays a vital role in fostering noble morals and character development in students, particularly adolescents. In this case, students of SMAN 3 Bogor, especially in the context of the holistic education era that emphasizes the integration of cognitive, affective, and psychomotor aspects. This article examines how Islamic religious education can systematically contribute to producing students who are not only knowledgeable but also virtuous. Through a review of previous literature and an analytical approach using descriptive-qualitative methods, this study highlights the gap in understanding the comprehensive implementation of Islamic religious education in student character development in modern educational institutions. The results of the study indicate that Islamic religious education effectively strengthens moral and character development through a contextual and adaptive approach to religious values, meeting the demands of the times. This study provides strategic recommendations for developing a holistic curriculum and character development based on Islamic values that are more integrative and applicable. Thus, this article is expected to enrich the academic treasury while providing a practical contribution to the development of religious education in the era of holistic education. Islamic religious education plays a strategic role as a bulwark against these challenges. Through the practice of worship, students can be shaped into resilient individuals who are not easily influenced by negative external factors. In conclusion, Islamic Religious Education plays a vital role in shaping students' character holistically from an early age.